Characteristics of Bamboo Leaf Ash Blended Cement Paste and Mortar - Akaninyene A Umoh; Isaac Abiodun Odesola (Civil Engineering Dimension, 2015)
The use of bamboo leaf ash as cement supplement can contribute to reduction in cost and environmental hazard associated with cement production as well as waste pollution caused by the littered bamboo leaves. Therefore, the characteristics of cement paste and mortar incorporating bamboo leaf ash were investigated. The results of the physical properties of the pastes were within the requirements stipulated by relevant standards while that of the mortar cubes indicated that the compressive strength generally increased with curing age, and that the mix containing 15% Bamboo Leaf Ash (BLA) by mass competes favorably with that of the reference mix at 28days and above. The water absorption and apparent porosity were observed to increase with increase in BLA content, while the bulk density decreases as the percentage of BLA increases from 5% to 25% by mass. The study concluded that 15% BLA replacing cement is adequate for the production of masonry mortar.